2012
DOI: 10.1016/j.healthplace.2012.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Does living by the coast improve health and wellbeing?

Abstract: It is often assumed that spending time by the coast leads to better health and wellbeing, but there is strikingly little evidence regarding specific effects or mechanisms to support such a view. We analysed small-area census data for the population of England, which indicate that good health is more prevalent the closer one lives to the coast. We also found that, consistent with similar analyses of greenspace accessibility, the positive effects of coastal proximity may be greater amongst more socio-economicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
204
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 317 publications
(238 citation statements)
references
References 16 publications
7
204
2
5
Order By: Relevance
“…Rural/urban differences were controlled for since childhood obesity has been shown to differ between urban and rural locations (HSCIC, 2013;Ridler et al, 2011) and since Wheeler et al (2012) found a stronger effect of coastal proximity on health and wellbeing in urban areas. The MSOA classification consists of four morphology codes -urban conurbation, urban city and town, rural town and fringe and rural village and dispersed -and a population density scale of 'sparse' or 'not sparse' is applied (Bibby and Brindley, 2013).…”
Section: Potential Confoundersmentioning
confidence: 99%
See 3 more Smart Citations
“…Rural/urban differences were controlled for since childhood obesity has been shown to differ between urban and rural locations (HSCIC, 2013;Ridler et al, 2011) and since Wheeler et al (2012) found a stronger effect of coastal proximity on health and wellbeing in urban areas. The MSOA classification consists of four morphology codes -urban conurbation, urban city and town, rural town and fringe and rural village and dispersed -and a population density scale of 'sparse' or 'not sparse' is applied (Bibby and Brindley, 2013).…”
Section: Potential Confoundersmentioning
confidence: 99%
“…Since a very low number of MSOAs (4) in the most rural class were within the 0-1km coastal category, the two rural classes were aggregated. A similar approach to urban/rural categorisation has been used in previous relevant studies (Mitchell and Popham, 2007;Wheeler et al, 2012), although these were based on higher resolution geographies. The percentage of greenspace (area density) was included as a potential confounder due to its association with childhood obesity (Cetateanu and Jones, 2014;Coombes et al, 2010).…”
Section: Potential Confoundersmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive associations between coastal proximity and indicators of general health, mental health and physical activity have been identified (Bauman et al, 1998;Witten et al, 2008), even after controlling for the level of green space in the living environment (Wheeler et al, 2012;White et al, 2013a;. In this paper, we explore the diverse therapeutic experiences sought out at the coast, drawing on the findings of an in-depth, interpretive, mixed methods study conducted with residents of two coastal towns in south west England.…”
mentioning
confidence: 98%